ALGORITMA HAZE DETECTION DENGAN MENGGUNAKAN HAZE INDEX PADA CITRA SPOT 6/7 - Sulyantara, D. Heri; Siwi, Sukentyas Estuti; Prabowo, Yudhi; Brahmantara, Randy Prima; Ulfa, Kurnia (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2018)
Multispectral satellite imagery often contaminated by haze and cirrus. It will reduce the accuracy of data interpretation. There are some haze detection methods that have been developed by the experts. However, haze detection is still one of the important challenges for the correction of multispectral optical data. The method is used on hazy SPOT 6/7 imagery. This method is developed based on the reflectance slope of blue and red visible bands. It is used based on the comparison that has been done in the STCHT, HOT, and SHT method. Adding the formula with different coefficients to get the optimum haze index value. Furthermore, the regression analysis has been done on the haze and cloud’s threshold value that is given by the applications of optimum haze index.